A social capital study - Yansyah, Fikri (Teorija in praksa, 2024)
Employing social capital theory as its framework, this study aims to investigate teachers’ understanding, perspectives, and level of implementation of curricula among teachers in Indonesia to identify embryonic inequalities and disadvantaged groups resulting from such policy practices. Through semi-structured interviews conducted in group settings, ten teachers’ voices were analysed using thematic analysis. The findings highlight the significant impact of low social capital among rural teachers on their grasp, perspectives, and implementation of curricula, in turn affecting student performance. Further, the study points to rural teachers and their students as vulnerable demographics affected by policy implementations, underscoring the imperative for policy reform.
Keywords: curricula; Družbeni vpliv; inequality; neenakost; Odločanje; podeželje; podeželski indonezijski učitelji; policy practice; politična praksa; rural areas; rural Indonesian teachers; social capital; socialni kapital; Socialni kapital (sociologija); teachers; Učitelji; učni načrti